La place du déplacement : réflexions sur la dimension mythique du Colonel Chabert. Issue 3 (December 2019) - FÄRNLÖF, HANS
Abstract : This study explores the poetic function of the mythical dimension of Balzac's short novel Le Colonel Chabert (1832). The mythical layer is clearly noticeable at the level of plot (a hero returns from war and reclaims his title, his possessions, and his wife) as well as in a modern version of catabasis (the colonel is unintentionally buried in a mass grave). Although the narrative contains clear reminders of the classical treatment of these elements, it presents a distorted and degraded version of them. Seen in the light of the evolution of Balzac towards becoming a writer who depicts contemporary society, this article interprets the displacement of the novel's mythical dimension as a way of disqualifying, through defective imitation, a fictional model rendered henceforth imperfect as a vehicle for the faithful rendering of reality.